1995
DOI: 10.1006/dbio.1995.1230
|View full text |Cite
|
Sign up to set email alerts
|

Stage-Specific Regulation of Murine Hsp68 Gene Promoter in Preimplantation Mouse Embryos

Abstract: In early mouse embryos, the major inducible heat shock gene, hsp68, is spontaneously and transiently activated at the two-cell stage and becomes heat-inducible around blastocyst stage. We have probed mouse embryo's ability to activate the promoter of this gene during preimplantation development by expression analysis of DNA constructs containing a reporter lacZ gene driven by hsp68 (hsp70A1) 5'-regulatory sequences of various length: (i) a full-length promoter (construct phsplacZ); (ii) a heat shock element (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 0 publications
3
36
1
Order By: Relevance
“…Normal ZGA in these embryos was evidenced by the expression of phspLacZ, a DNA construct directed by the hsp70.1 gene promoter (18), which is spontaneously activated during ZGA at the early 2-cell stage in the mouse (19,20) (Fig. 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Normal ZGA in these embryos was evidenced by the expression of phspLacZ, a DNA construct directed by the hsp70.1 gene promoter (18), which is spontaneously activated during ZGA at the early 2-cell stage in the mouse (19,20) (Fig. 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Since the initial two-dimensional gel electrophoresis analyses from Bensaude et al (3), numerous studies using different approaches have focused on the latter question (4,10,17,25,29,33,34,48). Recent studies (4,5,8,46) have revealed spontaneous transient expression of HSP70 lacZ or Luc hybrid genes at the two-cell stage, demonstrating that the sequences driving the spontaneous expression of HSP70 at the two-cell stage are localized within the HSP70 regulatory region included in these constructs. Furthermore, using this approach, Bevilacqua et al (5) have suggested that HSE which are bound by HSF are not involved in this spontaneous expression, since they obtained the same results with a mutant form in which the two proximal HSE sequences of the HSP70A1 promoter were deleted.…”
Section: Discussionmentioning
confidence: 99%
“…In embryos, enhancers are believed to relieve transcriptional repression which may result from particular components of chromatin structure. Reporter gene studies in both the mouse and the rabbit suggest the requirement for an enhancer begins at the 2-cell stage and continues with cleavage, although in the rabbit this requirement becomes even more restrictive for only particular enhancer sequences at the 8-to 16-cell stage (Wiekowski et al, 1991;Christians et al, 1994;Bevilacqua et al, 1995;Henery et al, 1995). Experiments to elucidate the mechanism underlying zygotic genome activation in bovine embryos have yet to be performed.…”
Section: Zygotic Gene Activationmentioning
confidence: 99%